Drug repurposing of clinically-approved drugs to target epithelial-mesenchymal transition using in silico analysis - Ong, Chun Hao (2021)
Epithelial-mesenchymal transition (EMT) is a process where epithelial cells transform into mesenchymal cells type like fibroblasts and myofibroblasts. In the process, the epithelial cells lose their epithelial phenotype with reduced apicalbasal polarity, while acquiring new mesenchymal traits with increased invasiveness. Accumulation of the mesenchymal cells also leads to the deposition of collagen in the extracellular matrix (ECM). It is well established that EMT contributes to the progression of fibrosis and cancer diseases. Therefore, a therapeutic method that inhibits the EMT process would be required. Transforming growth factor-beta (TGF-β) is a potent inducer of the EMT process. Previous studies had demonstrated that inhibition of the TGF-β receptor type 1 (also named ALK5) could inhibit EMT. However, current progress on the clinical development of novel ALK5 inhibitor has not been encouraging, often due to safety concerns of the novel drug leads. Since traditional de novo drug discovery comes with high risks, pharmaceutical companies have begun to use drug repurposing strategy for drug development. Drug repurposing or repositioning is a strategy of finding new therapeutic purposes for current existing drugs in the clinical market. Due to the fact that these drugs had been established to be safe for use, it would reduce the concerns of safety risks in human. In this study, drug repurposing approach was used to identify clinically approved drugs that can inhibit the EMT process via targeting TGF-β activity. Initial computational screening of clinically approved drugs via molecular docking had revealed several drugs with strong binding affinity (-10.8 to -9.6 kcal/mol) to ALK5 based on the reference range of known ALK5 inhibitors ranging from -11.2 to -9.5 kcal/mol. The shortlisted drug candidates include ergotamine, telmisartan, saquinavir, indinavir, nelfinavir and celecoxib. Subsequently, these drugs were tested experimentally in normal human bronchial epithelial cell line, BEAS-2B induced by TGF-β1. In the experiments, the morphology changes from cobblestone shape of epithelial cells towards elongated shape of mesenchymal cells were not prevented by the drug treatments. In addition, the drugs did not exhibit inhibitory effects on the downregulation of epithelial proteins (E-cadherin) and upregulation of mesenchymal proteins (vimentin and α-smooth muscle actin). Based on these observations, it is postulated that the results from molecular docking were false positives. It is recommended that future studies involving molecular docking method would require better optimization and improvement by performing cross-docking validation prior to screening and including the negative controls during screening. The tested drugs in this study could serve as negative controls in future screening against ALK5 protein.